Genomic analyses identify recurrent MEF2D fusions in acute lymphoblastic leukaemia - Gu, Zhaohui; Churchman, Michelle; Roberts, Kathryn; Li, Yongjin; Liu, Yu; Harvey, Richard C.; McCastlain, Kelly; Reshmi, Shalini C.; Payne-Turner, Debbie; Iacobucci, Ilaria; Shao, Ying; Chen, I-Ming; et al. (Nature communications, 2016)
Chromosomal rearrangements are initiating events in acute lymphoblastic leukaemia (ALL). Here using RNA sequencing of 560 ALL cases, we identify rearrangements between MEF2D (myocyte enhancer factor 2D) and five genes ( BCL9 , CSF1R , DAZAP1 , HNRNPUL1 and SS18 ) in 22 B progenitor ALL (B-ALL) cases with a distinct gene expression profile, the most common of which is MEF2D-BCL9 . Examination of an extended cohort of 1,164 B-ALL cases identified 30 cases with MEF2D rearrangements, which include an additional fusion partner, FOXJ2 ; thus, MEF2D- rearranged cases comprise 5.3% of cases lacking recurring alterations. MEF2D- rearranged ALL is characterized by a distinct immunophenotype, DNA copy number alterations at the rearrangement sites, older diagnosis age and poor outcome. The rearrangements result in enhanced MEF2D transcriptional activity, lymphoid transformation, activation of HDAC9 expression and sensitive to histone deacetylase inhibitor treatment. Thus, MEF2D- rearranged ALL represents a distinct form of high-risk leukaemia, for which new therapeutic approaches should be considered. Acute lymphoblastic leukaemia is characterized by chromosomal rearrangements. Here, the authors carry out RNA-sequencing on a large cohort of patients and identify recurrent rearrangements of MEF2D , which lead to increased transcriptional activity of the gene, and cellular transformation in vitro .